Pengaruh Pengintegrasian Teknologi Media Kahoot Pada Pembelajaran Pendidikan Agama Islam Di Sekolah Dasar - Zulkhi, Muhammad Dewa; Yulistranti, Amanda Eka; Damayanti, Latipia (Jurnal Gentala Pendidikan Dasar, 2023)
Students' learning achievement is caused by two main factors, namely internal factors and external factors. Internal factors include students' interests, talents, motivation and concentration, while external factors involve the role of family, friends and the school environment. The researcher has an interest in investigating how Kahoot Media Technology can be integrated in Islamic Religious Education learning in elementary schools. This research aims to evaluate the impact of integrating Kahoot Media in Islamic Religious Education learning. This research uses a mixed approach (mix method). There are several variables that are the focus of the research, namely responses and results, involving 25 students in class VI. The data analysis process was carried out using descriptive statistics. The integration of Kahoot Media was carried out at State Elementary School 146/I Jambi City. In analyzing responses and evaluation results, this research shows that the majority of students gave a "good" assessment of the integration of Kahoot Media in Islamic Religious Education learning in elementary schools